The Inner Hydration in Surfactant/Cholesterol Vesicles Differs from the Outer One: A Spectroscopic Investigation. Issue 19 (1st August 2022) - Pyne, Sumana; Pyne, Partha; Kumar Mitra, Rajib
Abstract: Vesicles contain two aqueous regions: inner core and outer‐to‐bulk . It has remained an open question whether hydration behaviour in the inner core differs from the outer‐to‐bulk region, mostly owning to the inability of the conventional spectroscopic techniques to deconvolute the contribution from these two regions. We, using THz‐FTIR spectroscopy (1.5–13.5 THz) experimentally probe the inner hydration of three differently charged surfactant/cholesterol vesicles composed of SDS, CTAB and Brij 30. Both dynamic light scattering (DLS) and atomic force microscopy (AFM) measurements affirm the transition from micelles to vesicles as cholesterol is added into surfactant solutions. FTIR measurements show that hydration behaviour changes significantly as micelles are converted into vesicles, the change been exclusively caused due to the formation of an inner core . Our measurements on the hydrogen bond stretch and librational motion of the inner hydration show distinct features compared to the overall hydration, which in turn is found to be surfactant type and cholesterol concentration dependent. Abstract : Vesicles contain two aqueous regions : inner core and outer‐to‐bulk. It remains unexplored whether the hydration behaviour of the inner core differs from that of the outer‐to‐bulk region, owning to the inability of conventional spectroscopic techniques to deconvolute the contribution from these two regions. Using THz‐FTIR spectroscopy, the authors probe the inner hydration behaviour of surfactant/cholesterol vesicles.